2022
DOI: 10.3389/fphys.2022.954815
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular CIRP induces acute kidney injury via endothelial TREM-1

Abstract: Introduction: Acute kidney injury is associated with elevated serum levels of extracellular cold-inducible RNA-binding protein (eCIRP), a damage-associated molecular pattern released during ischemia/reperfusion injury, hemorrhagic shock, and sepsis. It is unknown if circulating eCIRP and eCIRP-induced activation of receptor triggering receptor expressed on myeloid cells-1 (TREM-1), expressed on endothelial cells, play an important role in the pathogenesis of AKI.Methods: Male B6 wild-type (WT) and TREM-1−/− mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In the multivariate analysis, elevated levels of CIRP were identified as an independent risk factor for AKI. The mice experiment conducted by Siskind et al confirmed that CIRP can induce acute kidney injury by activating renal TREM-1 ( 26 , 27 ). Moreover, a prospective observational study conducted by Xia et al demonstrated that post-CPB levels of CIRP are associated with an increased risk of pulmonary dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…In the multivariate analysis, elevated levels of CIRP were identified as an independent risk factor for AKI. The mice experiment conducted by Siskind et al confirmed that CIRP can induce acute kidney injury by activating renal TREM-1 ( 26 , 27 ). Moreover, a prospective observational study conducted by Xia et al demonstrated that post-CPB levels of CIRP are associated with an increased risk of pulmonary dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…Upregulation of TREM-1 expression on monocytes and neutrophils by lipopolysaccharide (LPS), bacteria, and fungi has been demonstrated in vitro ( 17 ). Furthermore, increased expression of TREM-1 has been observed in sterile conditions such as autoimmune diseases ( 10 , 11 ), ischemia-reperfusion injury ( 18 ), myocardial infarction ( 19 ), and acute kidney injury ( 20 ). In these studies, the mechanisms of increased TREM-1 expression remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, neutrophils as well as other immune and non-immune cells also express TREM-1 to some extent. Inhibition of TREM-1 expressed on renal endothelial cells reduces the production of inflammatory cytokines and angiogenic factors after stimulation with DAMPs, potentially attenuating acute kidney injury ( 20 ). Furthermore, knockdown of TREM-1 on cardiomyocytes attenuates cardiomyocytes pyroptosis after LPS stimulation ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 92 ] In contrast, in eCIRP-induced mouse AKI, the mRNA expression of kidney injury molecule 1 (KIM-1) and NGAL in the kidneys of TREM-1 –/– mice was reduced. [ 93 ] In terms of mechanism, Pan et al [ 94 ] treated HK-2 cell lines in vitro with LPS. They found that TREM-1 promoted apoptosis and inhibited autophagy in HK-2 cells probably through the regulation of the NF-κB pathway.…”
Section: Role Of Trem-1 In Kidney-related Diseasesmentioning
confidence: 99%